Dynamic behavior and constitutive model of marble subjected to wet-dry cycling - Yongsheng Liu; Maolin Zhai; Zheng Yang; Zhongyi He (PLoS ONE, 2025)
The cyclic deterioration induced by periodic water-level fluctuations, combining dry-wet cycles and chemical corrosion, poses significant threats to the stability and durability of rock masses in reservoir areas. These effects become particularly critical under dynamic loading conditions. To investigate the mechanical characteristics and damage behavior of rock subjected to the coupled effects of dry-wet cycles, chemical corrosion, and dynamic loading, dynamic impact tests were conducted on marble specimens using a split Hopkinson pressure bar (SHPB) system. The tests considered various pH environments and different numbers of dry-wet cycles. By analyzing physical and mechanical parameters such as strength, elastic modulus, mass loss rate, and water absorption rate, and incorporating damage mechanics and the Lemaitre strain equivalence hypothesis, a dynamic constitutive model for marble was developed. The results indicate that as the number of dry-wet cycles increases, the mass loss rate, water absorption rate, peak strength, and elastic modulus undergo significant changes in the initial stages, which gradually stabilize in later stages. The degree of mechanical degradation under different chemical environments follows the order: pH = 4 > pH = 10 > pH = 7. Both dynamic compressive strength and elastic modulus increase with rising impact air pressure, demonstrating higher sensitivity to impact pressure than to pH variations or the number of dry-wet cycles. The established dynamic damage constitutive model effectively captures the stress–strain behavior of marble under dry-wet cycles and dynamic loading. The findings provide a theoretical basis for assessing the safety and stability of reservoir bank rock masses.